2021
DOI: 10.1186/s13071-021-05079-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the interaction between insecticide resistance-associated genes and malaria transmission in Anopheles gambiae sensu lato in central Côte d’Ivoire

Abstract: Background There is evidence that the knockdown resistance gene (Kdr) L1014F and acetylcholinesterase-1 gene (Ace-1R) G119S mutations involved in pyrethroid and carbamate resistance in Anopheles gambiae influence malaria transmission in sub-Saharan Africa. This is likely due to changes in the behaviour, life history and vector competence and capacity of An. gambiae. In the present study, performed as part of a two-arm cluster randomized controlled trial evaluating the impact of household screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…Consistent with recent studies carried out in the area of Bouaké [ 7 , 9 , 13 , 36 ], there was a high frequency of both kdr and ace1 R genes in An. gambiae and An.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with recent studies carried out in the area of Bouaké [ 7 , 9 , 13 , 36 ], there was a high frequency of both kdr and ace1 R genes in An. gambiae and An.…”
Section: Discussionsupporting
confidence: 90%
“…The existence of multiple mechanisms of resistance in the main vector, Anopheles gambiae sensu lato (s.l.) threatens the efficacy of vector control tools currently used in Côte d'Ivoire, including LLINs [9][10][11]. Meiwald et al [11] found that pyrethroid resistance is associated with significant overexpression of CYP6P4, CYP6P3, and CYP6Z1 in Anopheles coluzzii in Côte d'Ivoire.…”
Section: Introductionmentioning
confidence: 99%
“…Meiwald et al [11] found that pyrethroid resistance is associated with significant overexpression of CYP6P4, CYP6P3, and CYP6Z1 in Anopheles coluzzii in Côte d'Ivoire. High allelic frequencies of knock-down resistance (kdr) L1014F mutation (range: 0.46-1), relatively low frequencies of the ace-1R mutation in the acetylcholinesterase gene associated with target-site insensitivity to carbamates and organophosphates (< 0.5), and elevated activity of insecticide detoxifying enzymes (mainly mixed function oxidases (MFOs), esterase and glutathione S-transferase (GST)), have been reported in Côte d'Ivoire [5,7,10]. Recent laboratory (WHO tube and CDC bottle) bioassays against local pyrethroidresistant An.…”
Section: Introductionmentioning
confidence: 99%
“…Although some other studies have seen increased Plasmodium infection rates or intensity when at least one kdr allele was present 24,58 , others have identified no association 26,59 , Further, one investigation demonstrated no impact of functional knockdown of para on infection, instead suggesting that the kdr mutation could be in genetic linkage with a gene that impacts immunity 25 . Given our results, such linkage is however unlikely to have occurred in our selection process.…”
Section: Discussionmentioning
confidence: 98%